Expression alteration analyses in the transgenic Arabidopsis carrying soybean Histidine-containing phosphotransmitter gene under salinity stress condition - Chi Hung, Thai; Lan Xuan, Hoang Thi; Thien Quang, Nguyen; Phuong Thao, Nguyen (Vietnam Journal of Biotechnology, 2022)
Productivity of many crops is highly vulnerable to extreme external conditions.  Environmental stress factors such as drought and salinity have become more and more serious due to climate change and appear in many areas worldwide with higher frequency. As both drought and salinity belong to osmotic stress, they have similar negative effects on plant growth, development, and productivity as well as trigger similar stress responses by plants. In a previous study analyzing the expression profile in two soybean (Glycine max) cultivars with contrasting drought-tolerant phenotypes, a member of two-component system (TCS) in soybean, GmHP08, was proposed to associate with the plant tolerance capacity to drought. Subsequent in planta study confirmed its action as a positive regulator under drought conditions, as the transgenic Arabidopsis plants ectopically expressing GmHP08 acquired better drought tolerance. Following this, the presented research further explored the possible function of GmHP08 in mediating plant response to salinity. The obtained data from RT-qPCR analyses suggested that GmHP08 might positively enhance the salt tolerance of the Arabidopsis transgenic plants by altering the transcriptional abundance of several stress-related genes, including RD29A, RD29B, ABI5, SAG13, and CSD1. Activities of these genes are known to be associated with osmoprotection, senescence process, and antioxidation, which contribute to salt-tolerance ability of the transgenic plants. These results provided the first line of molecular evidence regarding GmHP08 function in plant response to salinity conditions. Therefore, extensive studies should be conducted in future studies to elaborate on the mechanisms by which this TCS member could improve various types of osmotic stress tolerance in plants.